Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.cub.2013.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Priming of Stomatal Sensitivity to Abscisic Acid by Leaf Microclimate

Abstract: Plant water loss and CO2 uptake are controlled by valve-like structures on the leaf surface known as stomata. Stomatal aperture is regulated by hormonal and environmental signals. We show here that stomatal sensitivity to the drought hormone abscisic acid (ABA) is acquired during leaf development by exposure to an increasingly dryer atmosphere in the rosette plant Arabidopsis. Young leaves, which develop in the center of the rosette, do not close in response to ABA. As the leaves increase in size, they are nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 43 publications
7
72
6
Order By: Relevance
“…It has been shown that stomatal responsiveness may be conditional on growth conditions (e.g. plants grown under very high humidity show reduced stomatal responsiveness to ABA; Pospíšilová, 1996;Pantin et al, 2013b;Arve et al, 2014). However, different growth conditions seem to be insufficient to explain the abovementioned differences between our results and those of McAdam et al ( , 2016b, even though different humidity regimes were used in our experiments.…”
Section: Strong Vpd Response Of Aba-deficient Mutantscontrasting
confidence: 55%
“…It has been shown that stomatal responsiveness may be conditional on growth conditions (e.g. plants grown under very high humidity show reduced stomatal responsiveness to ABA; Pospíšilová, 1996;Pantin et al, 2013b;Arve et al, 2014). However, different growth conditions seem to be insufficient to explain the abovementioned differences between our results and those of McAdam et al ( , 2016b, even though different humidity regimes were used in our experiments.…”
Section: Strong Vpd Response Of Aba-deficient Mutantscontrasting
confidence: 55%
“…Exposure to low RH can enhance stomatal ABA responsiveness in young leaves that are constantly in a microenvironment with high RH (Pantin et al, 2013b). This indicates that reduced RH is required to prime stomatal ABA responses, potentially via increased ABA levels, as ABA application can restore stomatal ABA responsiveness (Pantin et al, 2013b) and results in normal stomatal development (Fanourakis et al, 2011) in plants grown at high RH. However, in these reports, the RH that led to reduced ABA sensitivity was very high: 90% or more.…”
Section: Resultsmentioning
confidence: 99%
“…High relative air humidity during growth has been associated with longer and more open stomata (Torre et al, 2003;Nejad and van Meeteren, 2005;Fanourakis et al, 2011;Aliniaeifard et al, 2014), lower levels of ABA (Zeevaart, 1974;Nejad and van Meeteren, 2007;Okamoto et al, 2009;Aliniaeifard et al, 2014), and decreased stomatal responsiveness to ABA (Pospíšilová, 1996;Fanourakis et al, 2013;Pantin et al, 2013b;Arve et al, 2014). Exposure to low RH can enhance stomatal ABA responsiveness in young leaves that are constantly in a microenvironment with high RH (Pantin et al, 2013b). This indicates that reduced RH is required to prime stomatal ABA responses, potentially via increased ABA levels, as ABA application can restore stomatal ABA responsiveness (Pantin et al, 2013b) and results in normal stomatal development (Fanourakis et al, 2011) in plants grown at high RH.…”
Section: Resultsmentioning
confidence: 99%
“…In the rosette plant Arabidopsis, stomatal sensitivity to ABA is acquired during leaf development by exposure to an increasingly dryer atmosphere, while young immature leaves, which develop in the center of the rosette, do not close in response to ABA. 30 Taken together, during the process of leaf development, that means from immature to mature, from young to aging, its stomatal sensitivity to ABA initially increased, and then decreased again. The young mature leaves have the maximum stomatal sensitivity to ABA than both the young immature leaves and the senescing leaves.…”
Section: The Development Stage-specificities Of Pyr1/pyl/ Rcar Aba Rementioning
confidence: 99%
“…10,28 The different stomatal sensitivity to ABA between mature leaves and young leaves in Arabidopsis rosette is also due to their distinct surrounding microclimate. 30 It seems that exposure of a leaf for a long time (several days) to some environmental conditions generates a sort of memory in the guard cells that results in the loss of suitable responses of the stomata to closing stimuli, such as desiccation and ABA. 47 The involved secondary messengers in stomatal movement is also related with leaves water conditions or RH.…”
Section: Spatio-temporal Specificities Of Pyr1/pyl/rcar Aba Receptorsmentioning
confidence: 99%